2012
DOI: 10.1515/jpm.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum boron levels and lipid profile in pregnancies with or without gestational diabetes

Abstract: This preliminary study contributes to the limited information about the metabolic aspects of boron. Considering the evidence that boron acts as a regulator of energy substrate utilization, the effect of dietary boron on glucose metabolism deserves further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, a study confirmed that the maternal status of boron in normal and diabetic pregnancies is not correlated with lipids and boron levels. The serum lipids and boron levels in 15 non-gestational diabetic and 19 gestational diabetic women showed no significant change in levels of boron [ 22 ]. Another study demonstrated that boric acid and sodium pentaborate pentahydrate (NaB) showed inhibitory activities on adipogenesis in a cell model.…”
Section: Boronmentioning
confidence: 99%
“…However, a study confirmed that the maternal status of boron in normal and diabetic pregnancies is not correlated with lipids and boron levels. The serum lipids and boron levels in 15 non-gestational diabetic and 19 gestational diabetic women showed no significant change in levels of boron [ 22 ]. Another study demonstrated that boric acid and sodium pentaborate pentahydrate (NaB) showed inhibitory activities on adipogenesis in a cell model.…”
Section: Boronmentioning
confidence: 99%
“…Nevertheless, other studies found no differences in serum lipid, lipoprotein, or apolipoprotein concentrations between pregnant women with or without GDM (ref. 17,18 ). They showed an increase in total triglycerides and triglyceride content in VLDL, LDL, and HDL particles.…”
Section: Lipid Changes In Normal Pregnancy and In Pregnancy With Gdmmentioning
confidence: 99%
“…To the best of our knowledge, the literature shows only ten metallomics studies published up to now, which have been performed on the serum/blood/plasma of pregnant women affected by GDM. [8][9][10][11][12][13][14][15][16][17] These studies are listed in the first ten rows of Table 1, which reports the samples analysed, the references, and the elements (listed in alphabetical order) having statistically different concentrations between DM and control groups. When considered together, these results do not allow the individuation of any definite key element for the pathology of GDM.…”
Section: Introductionmentioning
confidence: 99%